Социальные (исторические) движения в контексте социологических подходов - Гавриленко, И. (Социология: теория, методы, маркетинг, 2001)
The author analyzes social (historical) movements from various sociological points of view, like positivist, behaviorist and functional ones. There are also discussed the resource mobilization concept and the radical-class approach to the mass movements. The specific features of the “totalitarian movements’ so characteristic of the mass society are described. The author represents social movements as a kind of the conflict-consensus interactions.